Evaluating the Impact of a 12-Week Yoga Intervention on Cardiac Autonomic Function and Blood Pressure in Young Indian Adults with Primary Hypertension: A Randomized Controlled Study - Poli Borah; Masilamani Elayaraja; Jasvir Ram; Mou Pramanik; Tadang Minu; Likha Eichir; Zilpha A Modi; Lakshyajit Gogoi; Karuppasamy Govindasamy (Kharkiv State Academy of Physical Culture, 2023)
Background. Hypertension is a significant health concern in India, particularly among young adults. High blood pressure is associated with an increased risk of cardiovascular diseases, including stroke and heart disease. One potential approach to managing hypertension is through non-pharmacological interventions, such as Yoga. Purpose. This randomised controlled trial aimed to assess the effects of a 12-week yoga intervention on cardiac autonomic function and blood pressure in young Indian adults with hypertension. Methods. A total of sixty-six patients with hypertension (age: 22.4 ± 0.9) were randomly allocated to either the Yoga Program Group (YPG) consisting of (n=33) participants who underwent the 12-week yoga intervention or the Control Group (CG) with (n=33) participants who did not receive any treatment. Assessments were conducted before and after the intervention period, measuring heart rate variability (HRV) and blood pressure. Results. A two-way mixed analysis of variance (ANOVA) revealed significant improvements in the YPG for several HRV parameters, including RR interval (p ≤ 0.001), RMSSD (p ≤ 0.001), NN50% (p ≤ 0.001), pNN50% (p ≤ 0.001), and HF (p ≤ 0.001). Additionally, LF (p ≤ 0.001) and LF/HF ratio (p ≤ 0.001) significantly decreased in the intervention group. Blood pressure parameters also demonstrated significant reductions (p ≤ 0.001) in the intervention group when compared to the control group. Conclusion. The findings of this study suggest that a 12-week yoga program positively impacts cardiac autonomic function and blood pressure in young Indian adults with primary hypertension. These results underscore the potential of Yoga as a non-pharmacological intervention for managing hypertension in this demographic.